Documentary film studies and the cuestion of the real - Campo, Javier (Universidad de Chile. Instituto de la Comunicación e Imagen, 2011)
The question of what is real has been a constant for the sciences. Film studies since the early days not only have had to deal with the question of what is real, but also with the plight of this "industrial art" highlighted by Gilles Deleuze, according to which the film is definitely not an art or a science. The documentary film inevitably brings to the fore the question of what is real, and it is urgent for researchers who intend to work with their films. This field of study is also divided between those who skip the real problem as the "visible" and who, in more recent studies, consider the real documented as a construction. The purpose of this work is to recover the film studies that purport to provide answers to this question for the real to lead the twin problems facing the documentary studies: (1) by studying a cinema (2) of the real.